Synthesis and purification of nano-sized titanium carbide particles through vacuum carbothermal reduction for enhanced mechanical, microstructural morphology, and tribological properties in friction stir processed A356-based aluminum composites - Shashi Prakash Dwivedi; Vijay Chaudhary; Shubham Sharma; Ashutosh Pattanaik; P Vijaya Kumar; Yashwant Singh Bisht; Varinder Singh; Mohamed Abbas; Dražan Kozak; Jasmina Lozanovic; Abhinav Kumar (Journal of Materials Research and Technology)
This study focused on the synthesis and purification of nano-sized titanium carbide (TiC) particles through vacuum carbothermal reduction under a hydrogen/argon atmosphere. The process involved the production of carbon-coated titanium precursors, followed by heating under vacuum conditions at 1500 °C for 2.5 h. The resulting products underwent additional treatment in either a hydrogen/argon (1:1) mixed gas or pure hydrogen gas. Experimental findings revealed that TiC powders exhibiting a single phase are obtained within a molar ratio of Ti to C ranging from 1:2 to 1:4. Adjusting the molar ratio of Ti/C in the precursors allowed for controlled variation in the particle size of the synthesized TiC powders, ranging from 50 to 80 nm. Treatment in hydrogen/argon mixed gas at 850 °C for 3 h resulted in TiC products with an impressive purity of 99.40%. The subsequent incorporation of 5% Nano-TiC-3 (Ti to C ranging from 1:3) as reinforcement into an aluminum alloy by Friction stir process technique demonstrated a remarkable 19.41% improvement in tensile strength, highlighting the efficacy of this specific reinforcement. The nano-TiC-3 reinforced composite exhibited uniform distribution without porosity. Additionally, a notable 50.81% improvement in hardness and the best wear resistance were observed for the 5% Nano-TiC-3 reinforced aluminum composite. This comprehensive study contributes valuable insights into the synthesis, purification, and application of nano-sized TiC particles, paving the way for the development of high-performance aluminum-based composites with enhanced mechanical and tribological properties.